Forecast of GDP per Capita Growth in Polish Regions 2006-2015 - Herbst, Mikołaj (Regional Barometer. Analyses & Prognoses, 2008)
The article offers a forecast of GDP per capita growth in Polish regions (NTS2) and subregions (NTS3) between 2006 and 2015, based on the past deviations of regional economies from the national growth path. The simulation shows that highest rates are expected in two metropolitan areas – Warsaw and Poznań. The Mazowieckie region (the one including Warsaw) will become the first to surpass the average level of GDP per capita in EU27. Although Poland will generally close the GDP gap to EU, further polarisation between regions is expected. The per capita income of the most lagging Polish regions will in 2015 reach (in real terms) the 2006 level of Polish national economy.